Customary Law as Part of the Reform Legal System in Indonesia - Kiki Kristanto; Christio Drakhma Dekapolis; Isno Pandowo (Focus Journal : Law Review, 2023)
Customary law is a law that was born even before Indonesia proclaimed its independence in 1945. Customary law is part of original law and has grown and developed in Indonesia so that it also influences the implementation of the Indonesian legal system. The development and renewal of Indonesian law should not forget the important parts of the building blocks of the Indonesian legal system, including Customary Law. In short, this writing using a qualitative descriptive method provides an overview of the important role of customary law which should always be part of the renewal of the legal system in Indonesia. Historically, the formation of the Indonesian legal system also departs from the concept of customary law that lives in Indonesian society which was ultimately influenced by the Dutch legal system when the Dutch colonized Indonesia. The concordance process of the Dutch legal system colored the formation of the Indonesian legal system which in fact could not be denied that it still left a residue in several parts of the Indonesian legal system such as the old version of the Criminal Code and the civil code. The development and renewal of the National Legal System according to the author should not leave material legal sources as the basis for the formation of a legal system that reflects the spirit of Indonesia. Material legal sources that are reflected in Pancasila, the ideals of Indonesian society, values, norms, kinship, deliberation, mutual cooperation, tolerance, and so on that characterize Indonesian society must be a priority scale in structuring the Indonesian legal system in the future, including part of cultural heritage in the context of customary law.